2018
DOI: 10.3892/or.2018.6599
|View full text |Cite
|
Sign up to set email alerts
|

Beclin1 overexpression suppresses tumor cell proliferation and survival via an autophagy‑dependent pathway in human synovial sarcoma cells

Abstract: Beclin1 is an important autophagy-related protein, which is involved in both autophagy and apoptosis. In recent years, the antitumor effect of Beclin1 has received increased attention. In the present study, we established a stable Beclin1-overexpressing cell line with SW982 human synovial sarcoma cells. We found that Beclin1 overexpression decreased the cell viability, inhibited proliferation and induced apoptosis in SW982 cells. The expression levels of Bcl-2 and PCNA were decreased, while the levels of cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
0
20
1
Order By: Relevance
“…One outcome of this unexpected neratinib biology was that the drug regulated the Hippo Pathway. Coordinated signaling by RAS proteins and the co-transcriptional regulators YAP and TAZ has been shown to promote tumor growth, invasion and chemotherapy resistance (2326). Individually, neratinib as well as [pazopanib + entinostat] exposure increased the phosphorylation of YAP and TAZ and interacted together to further enhance phosphorylation of the co-transcription factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One outcome of this unexpected neratinib biology was that the drug regulated the Hippo Pathway. Coordinated signaling by RAS proteins and the co-transcriptional regulators YAP and TAZ has been shown to promote tumor growth, invasion and chemotherapy resistance (2326). Individually, neratinib as well as [pazopanib + entinostat] exposure increased the phosphorylation of YAP and TAZ and interacted together to further enhance phosphorylation of the co-transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…In our sarcoma studies we also discovered that Rubicon knock down was significantly more protective against neratinib, [pazopanib + entinostat] and [pazopanib + entinostat + neratinib] when compared to Beclin1/ATG5. Although there are no published studies discussing LAP in sarcomas, significant literature exists defining the role of autophagy in the biology of sarcomas (2326). For example, over-expression of Beclin1 can promote autophagy-dependent sarcoma growth and resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in the present study, the autophagic response of OS cells was investigated by western blot analysis and mRFP-GFP-LC3 adenovirus assay. Beclin1, a protein whose levels are positively associated with the level of autophagy, was overexpressed in the two cell lines in a dose-dependent manner following treatment with PI-1840, and knowledge of its anticancer activity has been emerging in recent years (41). To inhibit autophagy of the OS cells, chloroquine was used, and subsequently a CCK-8 assay was performed to determine whether the PI-1840-induced autophagy could influence the survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…FLIP has been shown to inhibit LC3 lipidation by competitive interaction with ATG3, which in turn blocks autophagy [16]. Moreover, Zhu J., et al have shown that the inhibition of survivin through the use of siRNA enhanced autophagy by upregulating Beclin-1 [29]. Therefore, in order to explain the mechanism by which PRFR sensitizes TNF-α-induced autophagy, the modulatory effect of PRFR on TNF-α induced FLIP, Bcl-xl, and survivin expression levels was examined.…”
Section: Discussionmentioning
confidence: 99%